Manejo de malezas en Arroz, aplicando Herbicidas pre-emergentes formulados con diferentes gránulos en Juan Guerra San Martín - Perú - Vásquez García, Gidier (2000)
In order to determining the concentration or dose of Oxiadiargyl and Oxadíazon and their type of insert appropriate for the use of this herbicides. Likewise to determine the relation. ship Benefit - cost of the best alternative in the cultivation of rice (Oryza sativa L) to the transplant, one carries out the: present work between April and September of 1998, in Juan's War District, County of San Martin and Region San Martin, Iocated geographically to 66 38" South latitude and 72° 21' altitude West. Being their altitude 230 meters on the level of the sea. The conduction of the experiment one carries out in the experimental fields of the program National Rice, of the Experimental Station Coming" - INIA- Tarapoto. The experimental design used for most of the experiment was die block completely Randomizados (DBCR) with arrangement factorial de 2x3x2 with 3 repetitions and 2 Witness. Two granulated herbicides were studied with three concentrations or dose by “herbicide" each herbicide with their respective one Insert either Crocol and Socol (Fine and thick) and it is like it continues: T1(Oxiadiargyl + Crocol to dose 100 g i.a/50 Kg); T2(Oxiadiargyl + Crocol to dose 120 g i.a/50 Kg); T3(Oxiadiargyl + Crocol to dose 150 g i.a/SO Kg); T4 (Oxadíazon + Crocol to dose 240 g i.a/50 Kg); T5 (Oxadíazon + Crocol to dose 300 g i.a/50 Kg); T6 (Oxadíazon + Crocol to dose to 350 g i.a/50 Kg); T7 (Oxiadiargyl + Socol to dose 100 g i.a/50 Kg); T8 (Oxiadiargyl + Socol to dose 120 g i.alSO Kg); T9 (Oxiadiargyl + Socol to dose 150 g ia/50 Kg); T1O (Oxadíazon +Socol to dose 240 g i.a/50 Kg); T11 (Oxadíazon + Socol to dose 300 g i e/50 Kg); T12 (Oxadíazon + Socol to dose 350 g i.a/50 Kg); T13 (Witness with manual deshierbo) and T14 (absolute Witness). The gross area of the parcel 60 m2, the experimental net area for parcel 42m2, the numbers of parcel blows are of 960, the numbers student y to evaluate for parcel it is of 672. The total number of treatment or experimental units are of 42. The granulated herbicides are pre - emergent you applies one day after the transplante with dose of the commercial product of 300 gramos for each one of the treatments that is to say 60 m2. insecticide Cypermetrina was applied to a dose of 15 cc For 15 liters of water, the die 13 days after the siembra to control Hydrellia spp (.fly minadora) and Lyssorrhoptrus spp (gorgojito of water). You also applies a fungicidal Brummuconazol to dose of 20 cc. for backpack of 20 liters of water to prevent Pyricularia Burned grissea in neck and cob". These applications avoided the presence of plagues and illnesses with more frequency in the cultivation of rice to the transplante. The parameters that were evaluated were: Control of overgrowths, Count of overgrowths for square meter, Fototoxicidad. Weight of dry matter of overgrowths, weight of dry matter of rice, Yield in grain. Macollas Numbers for cob and weight of 1 000 grains. With the obtained yields. one carries out the economic analysis relating Cost - I Benefit of each treatment. The best results as fur the outlined objectives and to the control of" overgrowths it was obtained with the treatments T5 (Oxadiazon + Crocol to dose 300g i.a/50Kg) and T3 (Oxadiargyl + Crocol to dose 15Og i.a/5OKg) and controlling the main overgrowths like: Echinochloa crusgalli turkey Snot", Echinochloa colmumm Gram lefe, Cyperus rotundus" Coconut " Eclipta dawn " Botoncillo ", Ammania coccinea Stick of water", Jussiaea limifolia “Nail", Monochoria vagjnalis dog Ear", cyperus difformis Coquito" .lschaenum nigusum "Mazorquilla", Sphenocles zeylanica" spenoclea and Leptochloa uninervia blue Grass", As for the relationship Cost-benefit, the best altemative is the treatment Tl2(0xadiazon + Socol to dose 350g í.a/5OKg); that obtained a yield of rice shell for hectare of 7131.80 Kg/ha and with a net profit del 583,43 New Suns for hectare: turning out to be the but economic with 62, 99%